Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2010
DOI: 10.1002/cssc.201000142
|View full text |Cite
|
Sign up to set email alerts
|

Homogeneous Oxidation Reactions of Propanediols at Low Temperatures

Abstract: O2 reacts with propanediols via homogeneous pathways at 400–500 K. 1,2‐Propanediol forms CH3CHO, HCHO, and CO2 via oxidative CC cleavage and acetone via dehydration routes, while symmetrical 1,3‐propanediol undergoes dehydration and oxidative dehydrogenation to form, almost exclusively, acrolein (ca. 90 % selectivity). The products formed and their kinetic dependence on reactant concentrations are consistent with radical‐mediated pathways initiated by O2 insertion into CH bonds in a β position relative to ox… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
46
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 39 publications
(52 citation statements)
references
References 32 publications
6
46
0
Order By: Relevance
“…Besides these two aldehydes, a trace amount of acetone was also observed but is not plotted in the figure. The results are consistent with the findings of PG thermal oxidation reported by Diaz et al [9] and Bekki et al [16]. When the reactor temperature reached 215°C, formaldehyde and acetaldehyde began to increase noticeably.…”
Section: Resultssupporting
confidence: 93%
See 1 more Smart Citation
“…Besides these two aldehydes, a trace amount of acetone was also observed but is not plotted in the figure. The results are consistent with the findings of PG thermal oxidation reported by Diaz et al [9] and Bekki et al [16]. When the reactor temperature reached 215°C, formaldehyde and acetaldehyde began to increase noticeably.…”
Section: Resultssupporting
confidence: 93%
“…In fact, the achievable temperature inside e-devices ranges up to 350°C [7, 8], sufficiently high to decompose PG or GL. Diaz et al [9] studied the homogeneous oxidation reaction of PG in a 10% O 2 /He mixture at different temperatures and concluded that PG can be easily oxidized at as low as 127–227°C to form formaldehyde, acetaldehyde, and carbon dioxide via oxidative C-C cleavage and to form acetone via a dehydration route. The dehydration of GL to yield acrolein is another well-known reaction in organic chemistry.…”
Section: Introductionmentioning
confidence: 99%
“…The results revealed that GLY can be directly oxidized to C3 acids (glyceric), and leads to C2 (glycolic) and C1 (formic) acids through a C–C cleavage reaction. This kind of reaction has been reported elsewhere for various alcohols . Hydroxypyruvic acid, mesoxalic acid and CO 2 were not observed in this work, although they have been reported elsewhere .…”
Section: Discussionsupporting
confidence: 81%
“…Studies have reported widely varying carbonyl yields,24 with some exceeding those reported for combustible cigarettes 25. Produced carbonyls in ECIG aerosol was anticipated from the investigation of PG and VG pyrolysis in food chemistry and biomass fuel generation 26 27. Flavourants may present another potent source of ‘vaping toxicants’ 28…”
Section: Introductionmentioning
confidence: 99%